Development of polypropylene – based nanocomposites with good flame retardant properties - Yeo, Belina Xin Ying (2019)
This report provides a detailed documentation of the author’s final year project spanning over the duration of a year. The project is focused on the development of polypropylene (PP)-based nanocomposites with good flame-retardant properties. PP is the 2nd most used polymer after polyethylene for a variety of applications such as packaging and automobiles. However, PP is highly flammable, which makes it a safety hazard in the case of a fire. Hence, PP is often mixed with flame retardant additives to improve its flame retardancy. However, current popular flame retardants which are halogenated releases toxic gas. Thus, the motivation for this project to innovate new environmentally friendly flame-retardant additives to be compounded with PP for its use in automobiles. The strategy proposed targets specifically phosphorous and nitrogen-based flame retardants together with nanoclay. After the flame-retardant additives are synthesized, characterization was carried out – thermogravimetric analysis to confirm the molar ratio, fourier-transform infrared spectroscopy and scanning electron microscopy to confirm the bonding. Followed by compounding, and a preliminary flammability test referenced from UL94 50 W (20 mm) vertical burning test. This study covers 2 strategies which have yielded positive results on flame retardancy. Despite so, further optimization and characterization work is advised before reaching the best flame retardancy properties. Thus, the author recommends continuing with optimization on the amount of fillers needed in PP for sufficient flame retardancy to be commercialized, followed by mechanical strength testing for the use in automobiles.